AKIBAT HUKUM BAGI KREDITUR TERHADAP PENGIKATAN SURAT KEPUTUSAN PENGANGKATAN APARATUR SIPIL NEGARA SEBAGAI JAMINAN KREDIT APABILA TERJADI WANPRESTASI - Apritania Putri Setya Maratantri; Umi Khaerah Pati (Jurnal Privat Law, 2026)
The civil servant receiving credit may use the Civil Service Appointment Decree (SK ASN) as collateral. However, SK ASN is not a type of security that can be used as collateral, such as fiduciary or pawn. Because it cannot be used as collateral, the practice of ensuring SK ASN does not give rise to property rights. If there is a default, it causes problems, particularly for kreditor. This is normative legal research with a conceptual approach that uses primary and secondary legal materials, as well as data collection techniques in the form of literature studies. The findings revealed that SK ASN is not a collateral object. When a debtor defaults, the characteristics of SK as a valuable letter differ from those of securities that can be liquidated or transferred as debt repayment. SK ASN is only a security guarantee for banks whose position is equivalent to promissory notes. In the event of a default, the consequences of creditors are not prioritized in the repayment of the loan. As a result, the creditors' position is that of a competing creditor, as specified in articles 1131 and 1132 of the civil code. However, civil servant SK has its own risk and profit as a guarantee that is taken into account by a bank when granting credit.